Sanksi Hukum Pembunuhan Berencana Menurut Pasal 340 KUHP dan Hadits Shahih Imam Bukhari No. 6878 - Azka Habibah; Tajul Arifin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research examines the sanctions against premeditated murder within the framework of Indonesia's positive law and Islamic law. The study focuses on analyzing Article 340 of the Indonesian Criminal Code and Hadith Sahih al-Bukhari No. 6878 as primary sources. The method employed is descriptive-analytical with a normative juridical approach, using literature review and qualitative analysis. The findings reveal that both legal systems regard premeditated murder as a serious violation of the right to life. The imposed sanctions aim not only to punish but also to protect social stability and uphold human dignity. The maqāṣid al-sharī‘ah approach, particularly the principle of protecting life, serves as a fundamental basis for these sanctions. This study recommends the integration of substantive justice values and the protection of the right to life in the future development of the national criminal law system.